2009
DOI: 10.1074/jbc.m804073200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Leukemia-associated RhoGEF by Gα13 with Significant Conformational Rearrangements in the Interface

Abstract: The transient protein-protein interactions induced by guanine nucleotide-dependent conformational changes of G proteins play central roles in G protein-coupled receptor-mediated signaling systems. Leukemia-associated RhoGEF (LARG), a guanine nucleotide exchange factor for Rho, contains an RGS homology (RH) domain and Dbl homology/ pleckstrin homology (DH/PH) domains and acts both as a GTPase-activating protein (GAP) and an effector for G␣ 13 . However, the molecular mechanism of LARG activation upon G␣ 13 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…3a). Using surface plasmon resonance, the first study showed that G␣ 13 could interact not only with the RH but also with the DH/PH and C-terminal regions of LARG (Suzuki et al, 2009b), consistent with earlier observations using coimmunoprecipitation (Wells et , 2003). The presence of all three domains (RH, DH, and PH) was required for formation of the highest affinity complex, and the K204A mutation of G␣ 13 , which abrogates binding to the RH domain (Nakamura et al, 2004;Grabocka and Wedegaertner, 2005), did not eliminate binding to the DH/PH domain.…”
Section: Heterotrimeric G Protein-regulated Rhogefs 115supporting
confidence: 73%
See 2 more Smart Citations
“…3a). Using surface plasmon resonance, the first study showed that G␣ 13 could interact not only with the RH but also with the DH/PH and C-terminal regions of LARG (Suzuki et al, 2009b), consistent with earlier observations using coimmunoprecipitation (Wells et , 2003). The presence of all three domains (RH, DH, and PH) was required for formation of the highest affinity complex, and the K204A mutation of G␣ 13 , which abrogates binding to the RH domain (Nakamura et al, 2004;Grabocka and Wedegaertner, 2005), did not eliminate binding to the DH/PH domain.…”
Section: Heterotrimeric G Protein-regulated Rhogefs 115supporting
confidence: 73%
“…Although membrane recruitment is one aspect of signal transduction to RH-RhoGEFs, additional interactions at the cell membrane involving the various structural domains and sequence motifs of the RH-RhoGEF are probably required for full activation (Bhattacharyya and Wedegaertner, 2003;Bhattacharyya et al, 2009). Indeed, there is evidence that G␣ 13 interacts with other regions in addition to the RH domain (indicated by red arrows) to stabilize a high-affinity complex and stimulate GEF activity (Suzuki et al, 2009b). Autoinhibition of basal activity is believed to be imposed by the cooperative actions of the N-terminal region and C-terminal tail of the RhoGEF, as well as by an acidic sequence in the RH-DH linker region .…”
Section: Heterotrimeric G Protein-regulated Rhogefs 115mentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinities between RH and G␣ 13 range between 10 nM to 1 M, depending on the specific RH domain and the state of the GTPase. 4 Binding of G␣ 13 to regions outside of the RH domain has been suggested (9,17), but the evidence is limited. The affinity between truncated p115 missing RH and activated G␣ 13 is low, such that no physical association between the two could be observed by size exclusion chromatography (Fig.…”
Section: Two Conserved Hydrophobic Motifs Outside Of the Canonical Rgmentioning
confidence: 99%
“…This raises the question of whether direct association between RH and G␣ 13 is actually required for the stimulation of GEF activity; it also suggests that regions outside of RH in p115 might interact with G␣ 13 during the activation process. There is evidence that activated G␣ 13 binds weakly to regions outside of RH; however, it has not been shown that the GEF activity of p115 is regulated by such interactions (9,17).…”
mentioning
confidence: 99%